2003
DOI: 10.1161/01.hyp.0000094557.36656.d0
|View full text |Cite
|
Sign up to set email alerts
|

l -Arginine Reverses p47phox and gp91phox Expression Induced by High Salt in Dahl Rats

Abstract: Abstract-Derangements in the production and degradation of reactive oxygen species (ROS) as well as nitric oxide (NO) have been implicated in cardiovascular diseases. We explored how supplementation with L-arginine, an NO synthase substrate, restores such derangements of ROS/NO systems in Dahl salt-sensitive, hypertensive (DS) rats. We detected an increase of NADPH oxidase activity, a key enzyme that produces superoxide, in the membrane fraction of the renal cortex derived from DS rats loaded with high salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 67 publications
1
55
3
1
Order By: Relevance
“…8 Thus, eNOS uncoupling seems to be a common mechanism of endothelial dysfunction, leading to reduced NO production and increased ROS production in the blood vessel wall. In DS rats, high salt intake induced the activation of NADPH oxidase , 24 and in another study, such activation increased ROS production, with subsequent endothelial dysfunction. 25 The production of ROS by NADPH oxidase oxidized BH4 to BH2 and caused eNOS uncoupling.…”
Section: Discussionmentioning
confidence: 78%
“…8 Thus, eNOS uncoupling seems to be a common mechanism of endothelial dysfunction, leading to reduced NO production and increased ROS production in the blood vessel wall. In DS rats, high salt intake induced the activation of NADPH oxidase , 24 and in another study, such activation increased ROS production, with subsequent endothelial dysfunction. 25 The production of ROS by NADPH oxidase oxidized BH4 to BH2 and caused eNOS uncoupling.…”
Section: Discussionmentioning
confidence: 78%
“…37 In vivo, Sprague Dawley rats fed a high-salt diet did not develop hypertension but exhibited increased urinary 8-isoprostane excretion and renal cortical gp91 phox and p47 phox subunit mRNA expression. 38 Although it has been shown that NADPH oxidase subunits are upregulated in SS rats fed a high-salt diet, 15 no study has previously shown an elevation in renal medullary NADPH oxidase in SS rats on a normal salt diet. Interestingly, in the present study, the subunit gp91 phox was not upregulated in the SS rat, whereas the p22 phox and p47 phox subunits were.…”
Section: Taylor Et Al Renal Medullary Nadph Oxidase and Hypertensionmentioning
confidence: 99%
“…[11][12][13] However, the source of the oxidative stress specifically in the renal medulla of SS rats and the contribution of O 2 ⅐Ϫ to salt-induced hypertension in this region is unclear. Several enzymes have been implicated as possible sources of elevated ROS in hypertension, including NADPH oxidase, 14,15 xanthine oxidase, 16 NO synthase (NOS), 17 cyclooxygenase, 18 and mitochondrial electron transport leakage. 19 It has been suggested that reductions of enzymes that scavenge ROS, such as superoxide dismutases (SOD), 20 catalase, and glutathione peroxidase (GPx), may also play a role.…”
mentioning
confidence: 99%
“…A decrease in the ratio of reduced tetrahydrobiopterin to oxidized dihydrobiopterin in the renal medulla has been shown to blunt NO production, and has been proposed to contribute to saltsensitive hypertension. 37 Oral L-arginine supplementation reverses p47 phox and gp91 phox expression induced by high salt in the renal cortex of Dahl rats, 38 suggesting that substrate supplementation can restore the imbalance between NO and reactive oxygen species, presumably by increasing NOSderived NO. In addition, L-arginine transport has been shown to affect NOS activity and NO production in the renal medulla.…”
Section: Regulation Of Nos Activitymentioning
confidence: 99%